The effects of capital structure on companies’ profitability: a study on industrial product companies listed on the main board of Bursa Malaysia / Saidatul Asha Zainal Abidin - Zainal Abidin, Saidatul Asha (Faculty of Business and Management, 2007)
The study aims to investigate effects of capital structure on profitability of the industrial product companies listed on the Main Board of Bursa Malaysia within six- year period. Data is collected on yearly basis for six consecutive years for 30 companies listed from secondary sources. Simple linear regression analysis is used in the estimation of functions relating the independent variable of debt equity ratio as the measures of capital structure and the dependent variables which are ROE, ROA and EPS. The results reveal that there are significant negative relationships between DER and ROE, ROA and EPS. From the results, all the dependent variables which are ROE, ROA and EPS show a significant relationship with DER. The study suggests that profitable companies should not depend on debt as their main financing option.